Analysis of the Meaning of Denotative in the Lyrics of Baghandu "Kutang Barendo": Philosophy of Language Study - Hasnah Faizah; Anisah Dzakirah; Dila Apri Kanisya; Elvira; Yusron Hadi Falah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The Baghandu oral literary tradition inherent in the Kampar community, Riau Province, is now facing semantic dynamics that threaten its integrity due to the loss of the younger generation’s ability to parse old vocabulary. This study aims to analyze the philosophy of language from the aspect of the denotative meaning of the Baghandu text “Kutang Barendo”. The analysis uses a thematic interactive model approach through a qualitative approach. The results of the study: 1) kutang in verse-1 refers to women’s underwear, while barendo refers to the decorative edge of the cloth with a decorative hole pattern; the lexicon tampuong sayak babulu refers to the part of the coconut shell that still has coconut fiber attached naturally; the word ati denotatively refers to internal body organs that are biologically related to human subjects; 2) the word baghandu in verse-2 refers to the ritual activity of lulling a child to sleep through a soothing singing rhythm; the lexicon crib denotatively refers to a simple tool for lulling a baby to sleep that is designed to be rocked rhythmically; the word baliuong has a clear and objective denotation as a carpentry tool that resembles an axe with a transverse blade; 3) the words boghek and ghingan in verse 3 are absolute physical measurements of the mass of an object that are independent of subjectivity; the lexicon jauo and dokek precisely refer to the measured distance of geographical space; 4) the word lolok in verse 4 refers to a state of total natural rest for the entire body and mental consciousness; the lexicon jago indicates a transitional state that marks consciousness from sleep; 5) the word sicerek in verse 5 refers to the endemic Clerodendrum serratum plant; lapako refers to a type of wild plant that grows in damp or swampy environments; the lexicon ketek is a physical measurement that contrasts with besar, while lalaku refers to actions, gestures, or physical action.